Biblical Authority and the Continental Reformation - Gerrish, B. A. (Scottish journal of theology, 1957)
That the distinctively ‘Protestant’ understanding of biblical authority can be grasped only by seeing it against its medieval background, may appear to be a truism. But the affirmation is necessary, if for no other reason, at least because the relationship of Protestantism to Catholicism has too often been interpreted as one of simple opposition in every respect. In part, however, the Reformers' understanding of biblical authority arises directly out of scholasticism, not by conscious opposition, but by unquestioning acceptance. The differentia of Protestantism cannot be defined simply by appeal to the so-called ‘formal’ and ‘material’ principles, unless the twin principles be themselves carefully defined. There was nothing new in the mere fact that the Reformers resorted to the Bible for verification of their theological convictions, nor even in their affirmation of the necessity of grace for salvation. The medieval Church had a rigorous doctrine of biblical inspiration, and it found grace as indispensable for justification as did the Reformers themselves.No doubt the earliest disciples took their view of inspiration and authority from Judaism. To begin with, their Scriptures were the Jewish Scriptures, and they themselves were all Jews. But it was natural enough that the Jewish doctrine of ‘verbal inspiration’ should persist even after the Church had become predominantly Gentile. The authority of Scripture is made to rest upon a theory of inspiration: the words of Scripture are binding because, in the last analysis, they are the Words of God.